Fostering pupils' lifelong learning competencies in the classroom: evaluation of a training programme using a multivariate multilevel growth curve approach. Issue 6 (1st November 2016) - Lüftenegger, Marko; Finsterwald, Monika; Klug, Julia; Bergsmann, Evelyn; van de Schoot, Rens; Schober, Barbara; Wagner, Petra
Abstract: Evidence-based interventions to promote lifelong learning are needed not only in continuing education but also in schools, which lay important cornerstones for lifelong learning. The present article reports evaluation results about the effectiveness of one such training programme (TALK). TALK aims to systematically implement the enhancement of lifelong learning in secondary schools by optimizing teaching in terms of developing pupils' competencies for lifelong learning. TALK is conducted within the framework of a three-semester course of studies for secondary school teachers. In order to evaluate the effectiveness of TALK, a questionnaire study with 1144 pupils was conducted in the form of a pretest–posttest–posttest design for both training and control groups. Multivariate multilevel growth curve analyses showed the benefit of TALK in terms of both pupils' perceptions of classroom instructions and their individual motivation. Finally, TALK's contribution to promote lifelong learning in schools is discussed and implications are given.